Review of the genus Hypostomus Lacépède, 1803 from rio Ribeira de Iguape basin, with description of a new species (Pisces, Siluriformes, Loricariidae) - Oyakawa, Osvaldo T.; Akama, Alberto; Zanata, Angela M. (Zootaxa, 2005)
Species of the loricariid genus Hypostomus Lacépède, 1803 from rio Ribeira de Iguape drainage (São Paulo and Paraná States, Brazil) are reviewed. Four species were found in the area: H. agna (Miranda-Ribeiro, 1907), H. ancistroides (Ihering, 1911), H. interruptus (Miranda-Ribeiro, 1918), and a new species H. tapijara. Hypostomus tapijara is distinguished from its congeners inhabiting rio Ribeira de Iguape basin by the presence of well defined large, dark, and roundish spots somewhat homogeneously distributed over body and fins, and by its relatively broad dorsal fin (interradial membranes apparently wider than in examined congeners from coastal Brazilian drainages). A key, descriptions and illustrations are provided for all species.